Biological control in Africa and its possible effects on biodiversity - Neuenschwander, Peter; Markham, R. (2001)
Biological control efforts in tropical Africa have been most often directed at invading exotic species and are conducted in rapidly changing landscapes, in which the flora, fauna and ecological interactions are imperfectly known. Faced with major threats to food production and ecosystem destruction, biological control practitioners have been obliged to take a pragmatic approach to minimize the risks of undesirable ecological effects. Work-shops convened under the auspices of the Inter-African Phytosanitary Council and the FAO brought together local slake holders and inter-national agencies to develop the various projects on classical biological control. Procedures required as pre-conditions for the importation of biological control agents have usually involved third country quarantine and host specificity tests, which -following the FAO code of conduct-have become more rigorous in recent years. Thus far, extensive pre-release testing of candidate control agents for the ability to attack native relatives of target species has not usually been required. Post-release documentation of impact has often included detailed ecological studies, but these have focused largely on agricultural habitats. The procedures followed and insights gained in relation to indirect effects are discussed in the light of classical biological control campaigns involving parasitoids and predators against exotic Homoptera, tetranychid mites, lepidopterous stemborers, thrips, the larger grain borer and water hyacinth, and the inundative use of fungaI pathogens against grasshoppers.